A new thermodynamic description of stable Cr-carbides for the third generation of thermodynamic database. (December 2017) - Li, Zhou; Mao, Huahai; Selleby, Malin
Abstract: An updated thermodynamic description of the stable Cr-carbides was obtained by applying the same models as used for the elements within the 3rd generation of thermodynamic databases. The Einstein model was used and a scaling factor was introduced to take into account the coupling effect between the stoichiometry (C to Cr ratio) and the structure of the compound. Using this model we could accurately describe the thermodynamic properties of these stoichiometric compounds using available experimental heat capacity data. The new description is now more physically sound and results in a better agreement with the experimental heat capacity data.